Answer: it’s -2,-4
Step-by-step explanation: since the dilation rule is 2/3 we take 2/3 of all the numbers. For example we took two thirds of -3 to get -2.
Answer:
5x^2-6x-10
Step-by-step explanation:
(2x^2-2x)-(-3x^2+4x+10)
2x^2-2x+3x^2-4x-10
5x^2-2x-4x-10
5x^2-6x-10
Answer:
12a + 24 = 6(2a + 4) is the equivalent expressions
Step-by-step explanation:
Given the terms ; 4, 12a, 6, 2a, and 24
There are two terms with unknown = 12a and 2a
but 12a = 2a x 6 .........(1)
from the last term = 24 = 6 x 4 ...........(2)
add both equation 1 and 2 = 12a + 24
12a + 24 = 6(2a + 4) is the equivalent expressions .
to VERIFY; Use a = 2
substitute into the expression ; LHS = RHS
= 12(2) + 24 = 24 + 24 = 48 (LHS)
FOR RHS = 6(2a+4) = 6(2x2 + 4)
= 6(4+4) = 48
Hence LHS = RHS
Simplifies to y=2x-12. slope intercept form is y=MX+b where m is slope and b is intercept do slope 4 and y intercept is -12